TANGGUNG JAWAB PRIBADI DIREKSI TERHADAP PERBUATAN HUKUM PERSEROAN YANG MERUGIKAN PIHAK KETIGA - Haspan Yusuf Ritonga; Azhari Yahya; Dahlan Ali (Jurnal Ilmu Hukum, 2016)
Abstract: Article 1 clause 1 of the Limited Company Act (UUPT) Number 40 Year 2017 states that the Limited Company is a legal entity. It is given a legal subject status who is responsible for any legal actions. However, based on the empirical reality, personal directors have been given responsibilities on the risk of legal action of the Limited Company. Duality reponsibilities in UUPT has created a responsibility repel between the Limited Company and the personal directors against whom a third party losses charged. This research was aimed to examine and explain how personal directors were responsible for the company legal act. The research method used was a juridical normative method including the law principles, the act legislation and the court decisions. The results showed that the decisions of judges who apply the imposition of personal directors’ liability against the act of legal company have been found with breakthroughs in the law and the basic principles of directors’ liability such as fiduciary duties, doctrine ultra vires and business judgment rule principles have been applied. However, for the uniformity of law application in society, UUPT should be updated by emphasizing personal directors’ liability against legal actions of the company which prejudice the third party so the UUPT could protect both the Limited Company and community equally and fairly.Keywords: Legal entity, Limited Company Act (UUPT), personal directors’ responsibility, third party. Abstrak: Pasal 1 angka 1 (satu) Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas (UUPT) menyebut “perseroan” adalah badan hukum, ia diberi status subjek hukum yang bertanggung jawab atas setiap perbuatannya. Namun pada kenyataan empiris, direksi telah dibebani tanggung jawab terhadap resiko perbuatan hukum perseroan. Dualisme pertanggungjawaban dalam UUPT telah menimbulkan tolak menolak tanggung jawab perseroan dengan direksi terhadap siapa kerugian pihak ketiga dibebankan. Penelitian ini dimaksudkan untuk mengkaji dan menjelaskan bagaimana semestinya direksi bertanggung jawab terhadap perbuatan hukum perseroan. Metode penelitian yang digunakan adalah yuridis normatif, meliputi kaidah-kaidah hukum, peraturan perundang-undanga serta putusan-putusan pengadilan. Dari hasil penelitian, ditemukan putusan-putusan hakim yang menerapkan pembebanan tanggung jawab pribadi direksi terhadap perbuatan hukum perseroan dengan terobosan-terobosan hukum serta menerapkan asas-asas dasar pertanggung jawaban direksi seperti prinsip fiduciary duties, doktrin ultra vires dan prinsip bussiness judment rule. Namun demikian, untuk keseragaman penerapan hukum dalam masyarakat, UUPT perlu diperbaharui dengan mempertegas pengaturan tanggung jawab pribadi direksi terhadap perbuatan hukum Perseroan yang merugikan pihak ketiga, sehingga produk hukum UUPT tersebut akan melindungi perseroan dan melindungi masyarakat secara berimbang dan berkeadilan.Kata Kunci: badan hukum, UUPT, tanggung jawab pribadi direksi, pihak ketiga.